Rethinking the Role of Top-Down Attention in Vision: Effects Attributable to a Lossy Representation in Peripheral Vision - Rosenholtz, Ruth; Huang, Jie; Ehinger, Krista A. (Frontiers in Psychology, 2012)
Common wisdom in the field of human vision suggests that top-down selective attention is required in order to bind features into objects. Without selective attention, presumably we are unable even to distinguish such simple stimuli as a rotated T vs. a rotated L. Selective attention, in turn, is often described as volitional and involving intentionality, suggesting – implicitly or explicitly – that it requires awareness. The resulting implication that we might need so expensive (and possibly human) a resource as consciousness in order to perform so basic a function as perception is improbable and counter-intuitive. In fact, we can carry out complex sensorimotor tasks, seemingly in the near absence of awareness or volitional shifts of attention (“zombie behaviors”). More generally, the tight association between attention and awareness, and the presumed role of attention on perception, is problematic. We propose that under normal viewing conditions, top-down selective attention does have an effect, but is not the critical determinant of feature binding and perception. Recent work on the nature of the representation in early vision instead attributes significant information loss to limitations of peripheral vision. We argue that this lossy representation leads to perceptual ambiguities often interpreted as a lack of feature binding, but is sufficiently rich to explain performance in such complex tasks as recognizing the gist of a scene, noticing popout targets, and navigating. These results are consistent with the notion that (largely non-volitional) shifts of the point of gaze may bear the primary responsibility for determining the information available to the visual system. The available information, in turn, provides a key determinant of the visual system’s capabilities and deficiencies. This scheme dissociates basic perceptual operations, such as feature binding, from both top-down attention and conscious awareness.